FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWA MEMILIH PROGRAM STUDI PERHOTELAN PADA POLITEKNIK MANDIRI BINA PRESTASI - Olga Theolina Sitorus; Videlia Regina Br Ginting (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
The aims of this study is to analyze the factors that influence students choosing the Hospitality of Polytechnic Mandiri Bina Prestasi Study Prorgam which consists of job opportunities prospects, students interests, family support, the learning environtment on campus and the economic conditions of parents. The population in this study were students of the Mandiri Bina Prestasi Polytechnic Hospitality Study Program. Sampling using the slovin formula to the entire number of hospitality study program students class of 2017, 208 and 2019.The sample usedin this study is a number of 70 students from three different generations. Method of data analysis using multiple linier regression analysis method. Hypothesis testing using t test and F test. The result of the study shows that simultaneously the prospect of job opportunities, student interest, family support, the learning of environtment on campus and the economic conditions of the parents influenced the student’s decision to choose The Hospitality Study Program at The Mandiri Bina Prestasi Polytehcnic. While by partial shows that the prospect of the job opportunities does not have a significant effect on the choice of Hospitality Study Program, then student interest does not have a significant effect on the choice of Hospitality Study Program, family support also does not have a significant effect on the choice of Hospitality Study Program, the learning environtment on campus has a significant effect on the choice of Hospitality Study Program, and the economic condition of the parents does not have a significant effect on the choice of Hospitality Study Program .